2013
DOI: 10.1111/edt.12044
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 627 hospitalized maxillofacial–oral injuries in Xi'an, China

Abstract: Preventive strategies for maxillofacial-oral injuries due to traffic accidents should be emphasized and promoted in the first hand, especially for males, rural residents and those aged between 18 and 59 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
3
18
1
1
Order By: Relevance
“…The type of trauma most commonly observed in this study was facial fracture (80%), a result higher than that of Leles et al [17] in Brazil (51%) and of Jin et al [2] in China (64%). The studies of Gassner et al [3] in Austria (62.5%) and Leles et al [17] in Brazil (98%) reported a high proportion of soft tissue injuries.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The type of trauma most commonly observed in this study was facial fracture (80%), a result higher than that of Leles et al [17] in Brazil (51%) and of Jin et al [2] in China (64%). The studies of Gassner et al [3] in Austria (62.5%) and Leles et al [17] in Brazil (98%) reported a high proportion of soft tissue injuries.…”
Section: Discussioncontrasting
confidence: 65%
“…In contrast, Motamedi [10] in Iran, Brasileiro & Passeri [1] in Brazil and Jin et al [2] in China observed a high prevalence of mandibular fractures. Among the bones that form the facial skeleton, the nasal bones are those with the least resistance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…External causes (accidents and violence) are of substantial importance in public health, given their magnitude and impact on people's lives, particularly in developing countries [1][2][3]. Traffic accidents and physical violence are major causes of death among young adults.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies in the current clinical literature on the aetiology and types of injuries in the maxillofacial region. Such injuries show frequency variations that differ according to the geographical areas and socio‐economic status of the populations in different countries, or within the same country , and according to their sex and age distributions. Mandibular fractures are extremely frequent, and these account for 41.7–74.0% of all of the maxillofacial fractures in previously reported clinical studies .…”
Section: Discussionmentioning
confidence: 99%